1986
DOI: 10.1177/030006058601400205
|View full text |Cite
|
Sign up to set email alerts
|

Use of Carbamazepine in Acute Psychosis: A Controlled Study

Abstract: A randomized double-blind study was performed to compare the therapeutic effects of lithium and carbamazepine (CBZ) each administered in combination with chlorpromazine (CPZ) for 3 weeks in women with acute psychosis. Thirty patients were studied. The initial dose was 1200 mg/day for CBZ and 900 mg/day for lithium, and it was subsequently modified according to plasma levels and clinical indications. The dose of CPZ was free and depended on the severity of symptomatology. Both treatments produced a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Carbamazepine seems to exert an acute antimanic effect (e.g. 16–21). The efficacy of OXC in bipolar disorder has been suggested already in some trials in acute mania (22–24).…”
mentioning
confidence: 99%
“…Carbamazepine seems to exert an acute antimanic effect (e.g. 16–21). The efficacy of OXC in bipolar disorder has been suggested already in some trials in acute mania (22–24).…”
mentioning
confidence: 99%
“…Particularly in the uncontrolled studies, carbamazepine has often been added to previously ineffective regimens including lithium carbonate. The adequacy of carbamazepine alone in comparison to lithium has been reported in more recent studies (Bellaire et al, 1988;Lusznat et al, 1988;Watkins et al, 1987;Placidi et al, 1986), but still requires further c1arification. Moreover, the issue of whether there are differential subgroups of responders to one drug compared to the other also requires further study.…”
Section: The Anticonvulsant Carbamazepine In Affective Illnessmentioning
confidence: 84%
“…At least 12 double-blind randomised controlled trials were reported in the '80s and early '90s, showing that carbamazepine is superior to placebo and comparable to lithium and antipsychotics in the treatment of acute mania [72][73][74][75][76][77][78][79][80][81][82][83]. However, only six of these studies [72-75, 78, 83] have not been biased by the concomitant use of lithium and antipsychotics.…”
Section: Carbamazepinementioning
confidence: 99%